Stability dependent increases in liquid water with droplet number in the Arctic - Murray-Watson, R; Gryspeerdt, E (Copernicus Publications, 2022)
The effects of aerosols on cloud microphysical properties are a large source of uncertainty when assessing anthropogenic climate change. The aerosol-cloud relationship is particularly unclear in high-latitude polar regions due to a limited number of observations. Cloud liquid water path (LWP) is an important control on cloud radiative properties, particularly in the Arctic, where clouds play a central role in the surface energy budget. Therefore, understanding how aerosols may alter cloud LWP is important, especially as aerosol sources such as industry and shipping move further north in a warming Arctic. Using satellite data, this work investigates the effects of aerosols on liquid Arctic clouds over open ocean by considering the relationship between cloud droplet number concentration (Nd) and LWP, an important component of the aerosol-LWP relationship. The LWP response to Nd varies significantly across the region, with increases in LWP with Nd observed at very high latitudes in multiple satellite datasets, with this positive signal observed most strongly during the summer months. This result is in contrast to the negative response typically seen in global satellite studies and previous work on Arctic clouds showing little LWP response to aerosols. The lower tropospheric stability (LTS) was found to be an important control on the spatial variations in LWP response, strongly influencing the sign and magnitude of the Nd-LWP relationship, with increases in LWP in high stability environments. The influence of humidity varied depending on the stability, with little impact at low LTS but a strong influence at high. The mean Nd state does not dominate the LWP response, despite the non-linearities in the relationship. As the Nd-LWP sensitivity changed from positive to negative when moving from high to low LTS environments, this work shows evidence of a temperature-dependent aerosol indirect effect. Additionally, the LWP-LTS relationship changes with Nd, generating an aerosol-dependent cloud feedback. As the LTS is ...